ICP22 homolog of equine herpesvirus 1: expression from early and late promoters. - Holden, V R (1992)
The complete nucleotide sequence of the short region, made up of a unique segment (Us; 6.5 kb) bracketed by a pair of inverted repeat sequences (IR; 12.8 kb each), of the equine herpesvirus 1 (EHV-1) genome has been determined recently in our laboratory. Analysis of the IR segment revealed a major open reading frame (ORF) designated IR4. The IR4 ORF exhibits significant homology to the immediate-early gene US1 (ICP22) of herpes simplex virus type 1 and to the ICP22 homologs of varicella-zoster virus (ORF63), pseudorabies virus (RSp40), and equine herpesvirus 4 (ORF4). The IR4 ORF is located entirely within each of the inverted repeat sequences (nucleotides [nt] 7918 to 9327) and has the potential to encode a polypeptide of 469 amino acids (49,890 Da). Within the IR4 ORF are two reiterated sequences: a 7-nt sequence tandemly repeated 17 times and a 25-nt sequence tandemly repeated 13 times. Nucleotide sequence analyses of IR4 also revealed several potential cis-regulatory sequences, two TATA sequences separated by 287 nt, an in-frame translation initiation codon following each TATA sequence, and a single polyadenylation site. To address the nature of the mRNA species encoded by IR4, we used Northern (RNA) blot and S1 nuclease analyses. RNA mapping data revealed that IR4 has two promoters that are regulated differentially during a lytic infection. A 1.4-kb mRNA appears initially at 2 h postinfection and is an early transcript since its synthesis is not affected by the presence of phosphonoacetic acid, an inhibitor of EHV-1 DNA replication. In contrast, a 1.7-kb mRNA appears at later times postinfection and is designated as a gamma-1 transcript, since its synthesis is significantly reduced by phosphonoacetic acid. These IR4-specific mRNAs are 3' coterminal, have unique 5' termini, and would code for in-frame, overlapping, carboxy-coterminal proteins of 293 and 469 amino acids, respectively. Interestingly, the site of homologous recombination to generate the genome of EHV-1 defective interfering particles that initiate persistent infection occurs between nt 3244 and 3251 of UL3 (ICP27 homolog) and nt 9027 and 9034 of IR4 (ICP22 homolog). Thus, this recombination event would generate a unique ORF that would encode a potential protein whose amino end was derived from the N-terminal 193 amino acids of the ICP22 homolog and whose carboxyl end was derived from the C-terminal 68 amino acids of the ICP27 homolog.